Tulang Ikan Patin (Pangasius sp.) sebagai Sumber Kolagen Sabun Mandi Padat: Catfish Pangasius sp. Bone as Collagen Source for Solid Bath Soap - Firlianty; Elita Elita; Yanti Krismonita; Rario Rario; Natallo Bugar; Anang Najamuddin (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
This study aimed to determine the effect of catfish Pangasius sp. collagen addition on solid bath soap quality and the best treatment in the production process of Pangasius sp.- collagen soap. The collagen concentration was set at 0%, 3%, 6%, and 9%. The result showed that the soap has met the SNI requirement for solid bath soap. The best treatment was found in treatment D where the soap contained 9% collagen with the characteristic of 7.759% water content, 0.181% ethanol-insoluble material, 0.027% free fatty acid, and pH of 10.47.